Anatomical features of venous outflow from rat’s reproductive organs - N. A. Nikitin; A. V. Nikitina; A. V. Baitinger (Бюллетень сибирской медицины, 2012)
The venous drainage from reproductive organs of rats is described; new data on peculiarities of the venous drainage are obtained.Objects of study were adult Wistar white rats (20 animals). The animals have passed precision dissection of vessels in order to study anatomic peculiarities of venous drainage from the left spermary in male rats and internal genital organs in female rats in norm. It has been shown that the venous drainage from the left spermary follows the spermatic vein entering into the pampiniform plexus system, which continues into the single venous trunk, which, in its turn, divides into the ascending and descending veins. The descending vein runs into the common left iliac vein, while the ascending vein runs into the renal vein. The venous drainage from female reproductive organs follows through the uterine vein, which, taking the tubal and spermatic veins, runs from the left into the left renal vein and from the right into the caudal vena cava.